The Influence of Green Products on Purchase Decision Behavior in Generation Y and Z with Green Knowledge as an Intervening Variable - Murniati, Syifa Milenia; Widodo, Arry (Jurnal Aplikasi Manajemen, 2024)
Plastic waste is one of the causes of global warming and uncontrolled climate change, so that it becomes one of the causes of increasingly severe skin problems. Plastic waste in Indonesia is still an important environmental problem and is receiving more attention in various fields, including the beauty industry. The goal of this study was to determine the effect of green products on consumer purchasing decisions mediated by green knowledge on love beauty and planet products. A quantitative strategy with a causal descriptive approach was adopted. SMART PLS 3.0 software and the structural equation modeling (SEM) analytical approach. The research was conducted in the city of Bandung, and the sample technique utilized was accidental sampling with a total of 400 respondents. Based on the results of the descriptive analysis of the variables green product, green knowledge and purchasing decisions in the very good category and based on the SEM-PLS analysis it shows a positive and significant influence, which means that consumers' perceptions of love beauty and planet products are green products so that purchasing decisions mediated by green knowledge have been carried out well. The respondents who dominated this study were the Z generation group or born in 1997-2012. This happened because Z generation in Indonesia cares enough about environmental issues and participates in activities with environmental issues compared to other generations.